Strengthening urban producer organizations - Larbi, Theophilus Otchere; Cofie, Olufunke O.; Amoah, Philip; Veenhuizen, René van (2014)
The chapter presents the process and results from a project implemented in Accra by the Resource Centres on Urban Agriculture and Food Security (RUAF) Foundation to strengthen farmers’ organizations for innovative irrigated vegetable farming and marketing. One hundred urban farmers were organized into eight producer groups and trained on technical and organizational innovations along the vegetable value chain towards improved yield and income. Training was delivered through Urban Producer Field Schools (UPFS) on topics ranging from integrated plant production and protection principles, food safety and risk-minimization in wastewater use for irrigation to value addition for marketing. Farmers were also engaged in organized marketing, targeting niche markets.